EXPLORING MULTICULTURAL-BASED PROBLEM-BASED LEARNING MODEL AS A STRATEGY TO ENHANCE BASIC READING COMPREHENSION FOR INDONESIAN EFL STUDENTS - Utami, Elva; Arono; Wisma Yunita (Universitas Islam Ogan Komering Ilir Kayuagung, 2025)
This study explores the effectiveness of multicultural-based Problem-Based Learning (PBL) model in enhancing basic reading comprehension among English language education students at three universities in Bengkulu, Indonesia. The objective was to assess whether integrating multicultural themes into PBL could improve reading comprehension compared to traditional teaching methods. A total of 140 students participated, divided into an experimental group and a control group. The experimental group engaged with multicultural PBL activities, while the control group followed a conventional teaching model. Pretest and posttest scores were analyzed using paired-sample t-tests, revealing significant improvements in the experimental group’s reading comprehension (p < 0.05). In contrast, the control group showed minimal change (p > 0.05). Qualitative data from student surveys and observational checklists indicated increased engagement, motivation, and cultural awareness among students in the experimental group. The study concluded that a multicultural-based PBL model is an effective approach for enhancing reading comprehension and fostering intercultural competence. It recommends incorporating multicultural PBL into language teaching curricula to improve both reading skills and global awareness among students.